2020
DOI: 10.1007/s13272-020-00482-7
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the sooting propensity of aviation fuel mixtures

Abstract: Aromatic compounds occurring naturally in jet fuels are precursors for the formation of soot in the exhaust gas of jet engines. Directly emitted in cruising altitude, soot particles lead to the formation of contrails and clouds influencing the radiation balance of the atmosphere. Hence, a detailed knowledge on the effect of aromatics on the sooting behavior is of great importance, especially for the development of alternative synthetic jet fuels. Investigations on the sooting propensity influenced by the molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…The experimental set-up for the measurement of the sooting propensity is shown in Figure 2 and consists of four parts: (I) The preparation of the fuel-air mixture; (II) the burner; (III) the sampling probe; and (IV) the particle detection unit. The determination of the sooting propensity has already been previously described [13,14], so only a short description is given here. For the preparation of the fuel-air mixture (I), the liquid fuel is vaporized using a HPLC-pump (LC-20AD, Shimadzu) to feed the vaporizer [15].…”
Section: Determination Of the Sooting Propensitymentioning
confidence: 99%
“…The experimental set-up for the measurement of the sooting propensity is shown in Figure 2 and consists of four parts: (I) The preparation of the fuel-air mixture; (II) the burner; (III) the sampling probe; and (IV) the particle detection unit. The determination of the sooting propensity has already been previously described [13,14], so only a short description is given here. For the preparation of the fuel-air mixture (I), the liquid fuel is vaporized using a HPLC-pump (LC-20AD, Shimadzu) to feed the vaporizer [15].…”
Section: Determination Of the Sooting Propensitymentioning
confidence: 99%
“…However, aromatic compounds also exhibit lower gravimetric net heats of combustion (NHOC) and are more prone to incomplete combustion and particulate emissions. [9][10][11] Recent work has also shown that many cycloalkanes can effectively swell legacy nitrile rubber o-rings, [6][7][8] while nearly all synthetic kerosenes are compatible with modern fluorosilicone or Vitont-based engine seals.…”
Section: Resultsmentioning
confidence: 99%
“…The elimination of aromatic compounds results in a number of enhanced properties including increased gravimetric NHOC, improved combustion properties, and reduced particulate formation. [9][10][11] To realize these optimized blends, efficient routes for the production of bio-based cycloalkanes are required.…”
Section: Introductionmentioning
confidence: 99%
“…Soot emissions were correlated with the hydrogen content of the fuel, and soot reductions were achieved in the fuel with low aromatic content while increased soot emissions were detected for the alternative fuel with higher aromatic content and lower hydrogen content [25]. Richter et al [26] also looked at the aromatic content of different synthetic fuels and compared them to the traditional Jet A-1 fuel. They showed that hydrogen deficiency of the fuel is a good measure for sooting behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…They showed that hydrogen deficiency of the fuel is a good measure for sooting behaviour. Additionally, they revealed that the aromatics structure in the fuel plays a greater role in soot formation rather than its concentration [26].…”
Section: Introductionmentioning
confidence: 99%